Pengaruh Promosi Terhadap Penjualan Produk Pupuk Organik Hemal Bio Di Pt. Hemal Agrinusa Jakarta - Junaidi Hendro (Jurnal Ekonomi, 2018)
The purpose of this study was to determine and analyze the effect of promotion on the sale of Hemal Bio Organic Fertilizer Products. The method used is a quantitative method. The results showed an increase in sales, meaning that the promotions carried out by the company had an influence on product sales. It is evident from the results of the regression results that the Promotion variable has a value of 0.711. This is confirmed by testing with a tcount value of 5.462 and a ttable (95%:30-2) of 2,048, with a significance level or Pvalue = 0.000 meaning it is smaller than the significance level = 0.05. From these results, the test criteria are tcount > ttable and Pvalue < meaning H0 is rejected and H1 is accepted. In conclusion, promotion has a positive and significant effect on sales of Hemal Bio Fertilizer Products by PT. Hemal Agronusa, Jakarta.